Advertising strategies in the cosmetic clinics industry : a study of Wuttisak and Nitipon Clinics' advertising strategies - Peeraya Thongkruer; Winai Wongsurawat; Sununta Siengthai; Badir, Yuosre (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
It is interestingly challenging for companies that have competed in the fast-changing world such as cosmetic industry in Thailand where there are many strategies especially advertising strategy on television in order to carry out their business and even to become the dominant and the leader. This project presents the advertising strategies used by the dominants clinics in Thailand which are Wuttisak clinic and Nitipon clinic and also presents how both clinics react and compete to each other under game theory. Their advertising strategies can be obviously seen from each of their advertisings on television and their competitive actions under game theory can be assumingly analysed by relying on several reliable resources such as online business articles and business news. By initially focusing on customers instead of competitors, Wuttisak clinic decided to use a new way instead of a traditional way to play in this cosmetic industry which is bringing out the importance of beauty by using a number of celebrities to convey it through television advertisings. Focusing on the rivals, Nitipon clinic keep advertising as same as what Wuttisak clinic do. Short movie, Word-of-mouth interview, Korean and Thai trends, persuasive words or even sign, slide of life and celebrity endorsement can be considered as their both advertising strategies. It seems that celebrity endorsement might be one of the decisive factors that make Wuttisak clinic become a winner in this competition and the leader in this cosmetic industry
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Project (M.B.A.) - Asian Institute of Technology, 2014
Keywords: Wuttisak Clinic; Nitipon Clinic; Cosmetics industry; Advertising -- Cosmetics